Bahia State, Brazil : Ariculture Sector Risk Assessment - Arias, Diego (World Bank, Washington, DC, 2015)
The present study is part of an effort by the World Bank and the State of Bahia to assess agriculture sector risks as a contribution to the strategic economic development and poverty reduction agenda of the state government. It is composed of two phases: an agricultural sector risk identification and prioritization (volume one) and a risk management strategy and action plan (volume two). The study provides practical elements for the implementation of the Bahia sustainable rural development project - named Bahia Produtiva, which is currently implemented by Regional Development and Action Company of Bahia (CAR) and is financed by a World Bank loan. Risks in Bahia’s agricultural sector are highly concentrated in soybean, maize, cotton, cacao, fruits, vegetables, and beans. There are a number of relatively frequent (1 in 3, 1 in 5 and 1 in 10 year occurrence probability) risks that have moderate expected impact. These risks are climate (drought), pest and diseases, and price volatility. Although livestock production is greatly exposed to sanitary risks, Bahia has not suffered catastrophic animal or plant health events in recent years. Looking at risks from the combined perspective of their impact potential (moderate to critical) and management possibility (none to very high), severe drought and moniliase disease in cacao appear as the risks with the most critical potential impact and minimum risk management. Therefore, they require medium to long-term investment and strong preparation to cope. Considering output value as a measure of aggregated impact of risks in Bahia as a whole, the greatest challenges are drought, aggressive pests and diseases, and weeds resistant to herbicides in Western Bahia, taking into account the proportionally large economic size of that region. The present action plan reflects the strategic lines and includes some basic details on who, when, and how much is required for the implementation of the actions. This report presents the findings and conclusions of the first and second phases of the agriculture sector risk assessment for the state of Bahia.